CM‐FRAP–Continuum Mechanics‐Based Fluorescence Recovery After Photobleaching. Issue 1 (23rd January 2023) - Saito, Takumi; Deguchi, Shinji
Abstract: Fluorescence recovery after photobleaching (FRAP) is widely used to evaluate intracellular molecular turnover or repeated translocation of molecules using confocal laser scanning microscopy. While numerous models have been developed for the analysis of FRAP responses, in which chemical interactions and/or fast diffusion processes are involved, it is inherently difficult to evaluate the long‐term behavior of molecular turnover because of the presence of intracellular flow and microscopic deformation of bleached regions. To overcome these difficulties, we have developed a novel continuum mechanics‐based FRAP (CM‐FRAP) approach that enables simultaneous evaluation of long‐term molecular turnover and intracellular flow/deformation. Here we demonstrate the utility of CM‐FRAP by using actin molecules associated with stress fibers in rat aortic smooth muscle cells with clarification of the experimental setup and data analysis. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Plasmid construction and sample preparation Basic Protocol 2 : How to perform FRAP experiments Basic Protocol 3 : Data analysis based on CM‐FRAP